Sintesis dan Karakterisasi Pupuk Multinutrien Calcium-Ammonium-Phosphate (CAP) Berbahan Cangkang Kupang Merah - Nailah Rosikah, Nasywa; Rahmawati, Fajar Nanda; Sumada, Ketut (Dinasti Research, 2024)
Fertilisers and composites are two types of materials that can be used to improve soil fertility. However, these two materials have some differences. One of them is in the manufacturing process, fertilisers can be made in various ways, while the composite manufacturing process can only be done by biological processes. The objectives of this paper are (1) To determine the effect of acidity degree (pH) on the formation of Calcium-Ammonium-Phosphate particles, (2) To determine the optimisation of Calcium Ammonium Phosphate from red mussel shells by precipitation method, and (3) To determine the characteristics of Calcium-Ammonium-Phosphate produced using SEM-EDX and XRF analysis. The type of research used uses experimental research. The results and conclusions drawn are (1) The solubility of CaHPO4 decreases with increasing pH so that the weight of the resulting product increases in the precipitation method, (2) The best condition for making calcium ammonium phosphate fertiliser with red shell material is in the condition of red shell weight of 30 grams and pH 7, (3) The chemical composition contained in the CAP product with the condition of 20 grams of shell weight at pH 5 is Ca content of 74.76%, and phosphorus content of 23.5%, (4) The particle size at pH 3 weight of 20 grams ranges from 830 nm - 1970 nm and the particle size at pH 3 weight of 30 grams ranges from 1980 nm - 5220 nm. Therefore the fertiliser product does not include nano particles, (5) The CAP fertiliser product meets the SNI standards for NPK fertiliser and dolomite fertiliser.